Pengaruh Lingkungan Kerja Dan Self Efficacy Terhadap Kinerja Karyawan Yang Dimediasi Kepuasan Kerja Studi Kasus Pada PT UP3 Surakarta - Putri, Avinca Sabila Devari; Maimun, Muhammad Halim (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
The work environment, self-efficacy, and job satisfaction can influence employee performance in efforts to improve it. This study aims to determine how employee performance at PT PLN UP 3 Surakarta is affected by the work environment and self-efficacy, with job satisfaction acting as a mediator. A Likert scale questionnaire was used to collect quantitative data, with a sample size of 61 employees from PT PLN UP3 Surakarta. The results showed that there is no significant relationship between the work environment and employee performance, a significant relationship between self-efficacy and employee performance, a significant relationship between job satisfaction and employee performance, a significant relationship between the work environment and employee performance when mediated by job satisfaction, and a significant relationship between self-efficacy and employee performance when mediated by job satisfaction.